High Coronary Artery Calcium Score Is Associated With Increased Major Adverse Cardiac Events After Liver Transplantation. Issue 2 (6th January 2023) - Su, Amanda; Almazan, Erik; Sakulsaengprapha, Vorada; Shay, Jessica; Wittstein, Ilan; Hammami, Muhammad; Pustavoitau, Aliaksei; Rizkalla, Nicole; Alqahtani, Saleh; Woreta, Tinsay; Hamilton, James P.; Kohli, Ruhail; et al.
Abstract : Background: Liver transplantation (LT) candidates frequently have multiple cardiovascular risk factors, and cardiovascular disease is a major cause of morbidity and mortality after LT. Coronary artery calcium (CAC) scores are a noninvasive assessment of coronary artery disease using computed tomography. This study examines CAC scores and cardiac risk factors and their association with outcomes after LT. Methods: Patients who underwent LT between January 2010 and June 2019 with a pretransplant CAC score were included in this study. Patients were divided by CAC score into 4 groups (CAC score 0, CAC score 1–100, CAC score 101–400, CAC score >400). Major adverse cardiovascular events (MACEs) were defined as myocardial infarction, stroke, revascularization, heart failure, atrial fibrillation, and cardiovascular death. Associations between CAC score and MACE or all-cause mortality within the 5-y post-LT follow-up period were analyzed using Cox regression. Statistical significance was defined as P < 0.05. Results: During the study period, 773 adult patients underwent their first LT, and 227 patients met our study criteria. The median follow-up time was 3.4 (interquartile range 1.9, 5.3) y. After 5 y, death occurred in 47 patients (20.7%) and MACE in 47 patients (20.7%). In multivariable analysis, there was no difference in death between CAC score groups. There was significantly higher risk of MACE in the CAC score >400 group, with a hazard ratio 2.58 (95% confidence interval 1.05, 6.29). Conclusions: CAC score was not associated with all-cause mortality. Patients with CAC score >400 had an increase in MACEs within the 5-y follow-up period compared with patients with a CAC score = 0. Further research with larger cohorts is needed to examine cardiac risk stratification in this vulnerable patient population.